2013
DOI: 10.1371/journal.pone.0070711
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Dispersal Patterns within and between Atlantic and Mediterranean Populations of a Large-Range Pelagic Seabird

Abstract: Dispersal is critically linked to the demographic and evolutionary trajectories of populations, but in most seabird species it may be difficult to estimate. Using molecular tools, we explored population structure and the spatial dispersal pattern of a highly pelagic but philopatric seabird, the Cory's shearwater Calonectris diomedea. Microsatellite fragments were analysed from samples collected across almost the entire breeding range of the species. To help disentangle the taxonomic status of the two subspecie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 72 publications
2
33
0
Order By: Relevance
“…; see also Genovart et al. for a discussion of its taxonomic status). Scopoli's shearwaters nest in individual burrows, which are located on the ground in rock crevices.…”
Section: Methodsmentioning
confidence: 99%
“…; see also Genovart et al. for a discussion of its taxonomic status). Scopoli's shearwaters nest in individual burrows, which are located on the ground in rock crevices.…”
Section: Methodsmentioning
confidence: 99%
“…comm. ; Genovart et al ). Genetic differences between populations are consequently low (Genovart et al ) and exchanges of individuals among populations might also be sufficient to preclude significant variations in the composition of uropygial secretions, but no data support this for the moment.…”
Section: Discussionmentioning
confidence: 99%
“…Low survival rates in this species might be compensated for by recruitment, which was here estimated in the form of seniority probability and encompasses not only local recruitment but also immigration. Previous studies already suggested that even if the species is mostly philopatric (97%), there is non-negligible dispersal (particularly natal dispersal) between colonies (Genovart et al 2013b).…”
Section: A S E S T U D Ymentioning
confidence: 99%